PREVALENCE OF OBSTRUCTIVE SLEEP APNEA IN AN INDIAN POPULATION: USING STOPBANG QUESTIONNAIRE - Pattanaik, Snigdha; R, Rajagopal; Mohanty, Neeta; Pattanaik, Swati (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Obstructive sleep apnea (OSA) is a condition characterized by complete/partial obstruction of the upper airway that disrupts normal sleep pattern. It has become highly prevalent and negatively affects the quality of life. Reports show ≥4% of men and ≥2% of women, and mostly, the obese individuals are affected by OSA. OSA is independently associated with an increased likelihood of hypertension, cardiovascular disease, and diminished quality of life. Hence, it becomes a prime concern for health-care personnel to diagnose it at earliest. A screening tool is necessary to stratify patients based on their clinical symptoms, their physical examinations, and their risk factors. Thus, this study was taken up to assess the prevalence of OSA using the STOP-Bang questionnaire. Methods: A total number of 1012 participants were selected using random sampling technique from various community health camps for the study. The participants were asked to fill in the STOP-Bang questionnaire. All questionnaire respondents were precisely briefed about this study in a face-to-face interview. Data obtained from the survey were subjected to statistics, and descriptive analysis was done. Results: The prevalence of OSA was found to be 13.7% by using the Stop Bang questionnaire. It was found that the prevalence of OSA was highest in the age group of 50–59 (21.7%) and least in the age group of 18–29 (12.0%). Gender-wise distribution of OSA based on the scoring was seen to be more, among males (14.8%) and females showed a prevalence of 12.9%. Conclusion: This study concludes that the STOP-Bang method of screening showed a prevalence of 13.7%. However, the prevalence of OSA did not show any significant difference in various age groups; it was found that males had a higher prevalence of OSA compared to females.